Implementation of a Regional Training Program on African Swine Fever As Part of the Cooperative Biological Engagement Program across the Caucasus Region - De Nardi, Marco; Léger, Anaïs; Stepanyan, Tatul; Khachatryan, Bagrat; Karibayev, Talgat; Sytnik, Igor; Tyulegenov, Samat; Akhmetova, Assel; Nychyk, Serhiy; Sytiuk, Mykola; Nevolko, Oleg; Datsenko, Roman; et al. (Frontiers in Veterinary Science, 2017)
A training and outreach program to increase public awareness of African swine fever (ASF) was implemented by Defense Threat Reduction Agency and the Ministries of Agriculture in Armenia, Georgia, Kazakhstan, and Ukraine. The implementing agency was the company SAFOSO (Switzerland). Integration of this regional effort was administered by subject matter experts for each country. The main teaching effort of this project was to develop a comprehensive regional public outreach campaign through a network of expertise and knowledge for the control and prevention of ASF in four neighboring countries that experience similar issues with this disease. Gaps in disease knowledge, legislation, and outbreak preparedness in each country were all addressed. Because ASF is a pathogen with bioterrorism potential and of great veterinary health importance that is responsible for major economic instability, the project team developed public outreach programs to train veterinarians in the partner countries to accurately and rapidly identify ASF activity and report it to international veterinary health agencies. The project implementers facilitated four regional meetings to develop this outreach program, which was later disseminated in each partner country. Partner country participants were trained as trainers to implement the outreach program in their respective countries. In this paper, we describe the development, execution, and evaluation of the ASF training and outreach program that reached more than 13,000 veterinarians, farmers, and hunters in the partner countries. Additionally, more than 120,000 booklets, flyers, leaflets, guidelines, and posters were distributed during the outreach campaign. Pre- and post-ASF knowledge exams were developed. The overall success of the project was demonstrated in that the principles of developing and conducting a public outreach program were established, and these foundational teachings can be applied within a single country or expanded regionally to disseminate disease information across borders; overall, this method can be modified to raise awareness about many other diseases.